2010
DOI: 10.1002/cncr.25298
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in men with testicular cancer prior to adjuvant therapy

Abstract: BACKGROUND:Cognitive dysfunction experienced by individuals with cancer represents an important survivorship issue because of its potential to affect occupational, scholastic, and social activities. Whereas early efforts to characterize cognitive dysfunction primarily focused on the effects of chemotherapy, more recent evidence indicates that impairment may exist before systemic treatment. This study characterized cognitive dysfunction before adjuvant chemotherapy in a sample of men diagnosed with nonseminomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 33 publications
8
51
1
6
Order By: Relevance
“…One factor that was found to be associated with poorer cognitive function was higher doses of radiation therapy . Interestingly, two of 6 studies found that a large portion (between 38-46%) of newly diagnosed cancer patients demonstrated cognitive impairment prior to receiving chemotherapy (Hiniker et al, 2014;Wefel, Vidrine, et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One factor that was found to be associated with poorer cognitive function was higher doses of radiation therapy . Interestingly, two of 6 studies found that a large portion (between 38-46%) of newly diagnosed cancer patients demonstrated cognitive impairment prior to receiving chemotherapy (Hiniker et al, 2014;Wefel, Vidrine, et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…7,8,24,51 Poorer pretreatment cognitive function has been observed in patients with breast, 8,24 prostate, 51 and lung cancer. 52 Several factors may contribute to pretreatment changes in cognitive function, including psychological (depression or anxiety), persistent effects of general anesthesia following primary surgery, and disease-related factors such as extent of disease.…”
Section: Psychological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Cáncer testicular: al comparar a 70 pacientes tratados con cirugía+qui-mio terapia frente a 57 tratados con cirugía+radioterapia y 55 con cirugía sola, observaron que los participantes presentaban con frecuencia quejas cognitivas, independientemente de la modalidad de tratamiento, pero que solo un pequeño grupo de los tratados con quimioterapia manifestaba deterioro en pruebas neuropsicológi-cas (31) . En una muestra de 69 pacientes, evaluados tras la cirugía y antes de recibir quimioterapia, apreciaron un 43% de deterioro cognitivo, el deterioro fue evidente en función motora, aprendizaje verbal y función ejecutiva (32) . -Cáncer de ovario: en el estudio de 638 mujeres que recibieron quimioterapia, y otras 68 que no la habían recibido, se observa que las mujeres que habían recibido este tratamiento presentaban más quejas en memoria.…”
Section: Estudios Realizados En Poblaciones Con Diferentes Tipos De Cunclassified
“…cognitive functions -quality of life -sexuality -body image [8]. Výskum u mužov s rakovinou semenníkov (n = 69, použité metodiky: neuropsychologická batéria testov merajúca pozornosť, psychomotorické tempo, učenie, pamäť, reč, exekutívne a motorické funkcie, škála depresie CES-D, dotazník úzkosti STAIS), ktorý bol realizovaný po orchiektómii a pred adjuvantnou chemoterapiou, odhalil, že približne 48 % pa cientov vykazovalo v čase merania kognitívne zhoršenie, ktoré bolo podstatne väčšie, ako sa oča-kávalo vzhľadom k normám zdravej populácie.…”
Section: Introductionunclassified